Physiological responses of Bassia dasyphylla to drought during seed germination from different provenances - Chen, Juanli; Luo, Yongqing; Zhao, Xueyong; Li, Yan; Gao, Biao; Wang, Ruolan; Lou, Yuanxin; Mu, Junpeng (Frontiers in Ecology and Evolution, 2024)
Bassia dasyphylla is a prevalent herbaceous plant that exhibits enhanced resilience to dryness and elevated temperatures. It is frequently found in dispersed or grouped formation on sandy soil within steppe, semi-desert, and desert regions. Herein, we conducted the experiments to examine the growth and physiological traits of B. dasyphylla seeds originated from various regions in response to water scarcity. The study seeks to investigate the ability of these seeds to germinate under drought conditions and offer valuable insights for the development and breeding of high-quality germplasm resources in Inner Mongolia. The results demonstrated that B. dasyphylla originating from desert steppe (DS) exhibited a greater capacity to endure drought conditions in comparison to its counterparts from sandy land (SL). At a water potential of -0.30 MPa, the Seed germination rate from DS was 33.3%, while from SL it was 22.7%. With the increase in drought duration and intensity, germination rate, plumule length, both single-seed weight (SSW) and seed water content (SWC) of B. dasyphylla declined. The protective enzyme activity exhibited an initial increase, followed by a subsequent decline as the duration of the drought increased. Notably, we found that the protective enzyme activity from DS was higher than that from SL.During the initial and intermediate stages of dryness, the soluble sugar and protein of the plant from DS effectively inhibited the peroxidation of membrane lipids, whereas the osmoregulatory properties from SL did not have a significant impact. The findings suggest that the ability of B. dasyphylla to withstand drought conditions in DS can be attributed to its elevated amounts of protective enzymes and osmoregulatory factors, which serve to safeguard the cell membrane during periods of drought.